Tinjauan terhadap Isu Euthanasia Berdasarkan Perspektif Alkitab dan Hukum di Indonesia - Vandiano, Vardik (Dekonstruksi, 2025)
This paper examines the issue of euthanasia from both a Biblical and Indonesian legal perspective. Euthanasia remains a controversial ethical and legal issue, raising fundamental questions about the sanctity of life, moral autonomy, and human dignity. In Indonesia, euthanasia is considered a criminal act under current legislation. From a Biblical perspective, human life is sacred because it is created in the image of God, and therefore, intentional acts to end life are seen as morally impermissible. This study critically analyzes the legal stance in Indonesia, explores contemporary arguments supporting euthanasia such as personhood and quality-of-life ethics and contrasts them with theological arguments grounded in Scripture. The conclusion firmly rejects euthanasia as incompatible with both Indonesian law and Christian ethical principles, emphasizing the need for medical, pastoral, and spiritual care for those facing end-of-life decisions.